The scientist and the forger : probing a turbulent art world - Ragai, Jehane (World Scientific, 2018)
Foreword; Acknowledgements; Preface; Acronyms; Introduction; Scientific tools of the art detective; What motivates fraud? Why do we care so much about authenticity?; References; Chapter One Establishing the First Link in the Art Chain: Attribution; The curator and gallery dealer; The connoisseur and the art historian; The Ely Zakhai case -- connoisseurship's role in unraveling a Gauguin forgery; Stylistic and Morellian analysis; The Rembrandt Research Project; Rembrandt's Old Man With a Beard authenticated; References; Chapter Two Microscopy-Related Techniques; Optical microscopy.